2017
DOI: 10.1016/j.jamda.2017.06.032
|View full text |Cite
|
Sign up to set email alerts
|

Influences on Decision-Making Regarding Antipsychotic Prescribing in Nursing Home Residents With Dementia: A Systematic Review and Synthesis of Qualitative Evidence

Abstract: Antipsychotic prescribing in nursing home residents with dementia occurs in a complex environment involving the interplay of various stakeholders, the nursing home organization, and external influences. To improve the quality of antipsychotic prescribing in this cohort, a more holistic approach to BPSD management is required. Although we have found the issue of antipsychotic prescribing has been extensively explored using qualitative methods, there remains a need for research focusing on how best to change the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
52
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 63 publications
4
52
0
1
Order By: Relevance
“…They were perceived to improve the quality of life of people with BPSD and enabled everyone, including the GP, to cope with the constraints imposed by insufficient resources. A recent systematic review examined the influences on decision‐making on antipsychotic prescribing in nursing home residents and found that that to circumvent the problems of inadequate resourcing antipsychotics were “used” as cheap, fast, and effective staff members . In this current review, the benefits of antipsychotics were often over‐estimated and their potential harmful side‐effects were sometimes overlooked because these side effects were perceived to relate to longevity of life rather than quality of life.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…They were perceived to improve the quality of life of people with BPSD and enabled everyone, including the GP, to cope with the constraints imposed by insufficient resources. A recent systematic review examined the influences on decision‐making on antipsychotic prescribing in nursing home residents and found that that to circumvent the problems of inadequate resourcing antipsychotics were “used” as cheap, fast, and effective staff members . In this current review, the benefits of antipsychotics were often over‐estimated and their potential harmful side‐effects were sometimes overlooked because these side effects were perceived to relate to longevity of life rather than quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…In this current review, the benefits of antipsychotics were often over‐estimated and their potential harmful side‐effects were sometimes overlooked because these side effects were perceived to relate to longevity of life rather than quality of life. Similarly, the systematic review on prescribing influences in nursing home residents found that inadequate knowledge of the risks and benefits of antipsychotic prescribing in dementia enabled inappropriate prescribing . However, the benefit of antipsychotics in BPSD is minimal and many of the side effects, such as extrapyramidal symptoms and sedation, occur in the short term.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, non-pharmacologic treatment strategies have shown to improve NPS without the complicated side effect profile of medications. It is important to recognize that lack of training of caregivers, poor person-centered care, understaffing of healthcare centers, and lack of understanding of the natural progression of dementia can lead to inadequate assessment of NPS, poor implementation of non-pharmacologic strategies, as well as the overuse of pharmacologic agents (especially antipsychotics) [90]. In addition to increased availability and easy implementation of non-pharmacologic measures, consideration of deprescribing can result in improvement of NPS in elderly patients with dementia.…”
Section: Deprescribingmentioning
confidence: 99%